Intraoperative development of contralateral extradural hematoma during evacuation of traumatic acute subdural hematoma: A rare cause of malignant brain bulge during surgery - Singh, Manmohan; Ahmad, Faiz Uddin; Mahapatra, AK (Indian Journal of Neurotrauma, 2005)
Intraoperative development of epidural hematoma (EDH) is an unusual happening. We report a 36-year-old female who developed severe brain bulge while she was being operated for a traumatic left fronto-temporal acute subdural hematoma. Immediate post-operative CT scan revealed a massive contralateral EDH, which was subsequently evacuated. When a craniotomy is performed for a traumatic hematoma, intraoperative severe brain swelling should alert the surgeon about possibility of contralateral EDH formation especially if there is contralateral skull fracture.
Keywords: brain swelling; extradural hematoma; head injury; skull fracture; traumatic subdural hematoma